Regional disparities and dynamic evolution of suicide prevention and intervention efficiency in Japan - Tang, Yin (Frontiers in Public Health, 2025)
IntroductionThis study investigates the cost-effectiveness of suicide prevention and intervention (SPI) efforts by prefectural governments in Japan. It represents the first application of a public sector efficiency evaluation model to assess government SPI initiatives. The research aims to identify spatial disparities and dynamic evaluation in SPI efficiency, providing actionable insights for policymakers.MethodsWe employed a three-stage Modified Slacks-Based Measure of Super Efficiency to evaluate the SPI implementation efficiency of prefectural governments. This approach accounted for exogenous environmental and stochastic factors to isolate actual managerial efficiency. Additionally, the Luenberger productivity index was utilized to analyze the changes in SPI efficiency over time, focusing on the contributions of technological advancements and efficiency improvements.ResultsThe analysis revealed significant spatial disparities in SPI efficiency across prefectural governments. However, a substantial portion of these differences was attributable to exogenous environmental and stochastic factors, indicating relatively limited variations in actual managerial efficiency. The Luenberger productivity index indicated an overall upward trend in SPI productivity, driven primarily by technical change. Conversely, the analysis highlighted a decline in efficiency changes, predominantly due to reduced scale efficiency.DiscussionThe findings underscore the importance of considering external environmental and stochastic factors when evaluating SPI efficiency. While technical advancements have positively influenced SPI productivity, policymakers should address the deteriorating trend in scale efficiency changes to ensure sustainable improvements in efficiency. Strategies that balance technical change and efficiency enhancements are essential for optimizing local SPI efforts.